Yen bhule nā yāi - Ghosha, Śobhā, 1903- (Bariśāla Sebāsamiti, 1983)
Collection of sample narratives in the local dialects of Dhaka, Barisal, Chittagong, and Sylhet districts of Bangladesh, with rendition into modern Bengali.